Towards the Development of a Sustainable Procurement Framework for Improved Operational Efficiency in Donor-funded Procurements in the Zimbabwean Public Health Laboratory Services - Mayavo, Crossman (University of the Witwatersrand, Johannesburg, 2023)
The governments in sub-Saharan African countries seem to have failed to fund public health medical laboratory services adequately, and the donors have taken over such critical services. This study focused on developing a sustainable procurement framework for improved operational efficiency in donor-funded procurements in the Zimbabwean public health medical laboratory services. The study aimed to examine the donor-funded procurements processes followed by the public health medical laboratory services in Zimbabwe, to establish the effectiveness of donor-funded procurements in the medical laboratory services, to examine the determinants for donor-funded procurement for public health medical laboratories in Zimbabwe, and finally to examine the moderating effect of government policy on donor-funded procurement in the public health laboratory system. The study integrates Transaction Cost Economics, Person-Situation Interaction, and Agency theories to support the research’s argument. Guided by the pragmatism philosophy and the descriptive-exploratory nature of the research objectives, the research utilised mixed research methods in which 214 questionnaires were used while seven interviews were held with provincial scientists. The research results revealed that the donor-funded procurements processes followed by the public health medical laboratory services in Zimbabwe might be strengthened by close collaboration between the government and the donor community. The determinants of donor-funded procurement played a crucial mediating role between effective donor-funded procurement, donation requirement process, and donation recipient process. The study revealed that government policy plays a positive moderating role among the variables and effective donor-funded procurement. The Structural Equation Modelling revealed that the determinants of donor-funded procurement are the mediators among the variables and shows the direct relationship between the donation requirement, donation recipient preparation and donation implementation, and government policy as the moderator between effective donor-funded procurement and the expected procurement functions. The research findings could be of more importance as the laboratory is a crucial sub-health department that should provide accurate and reliable results for patient management, and the essential public health services entail that there should be equity in the health of all people, achievable through policies and systems that are actively promoted in the health systems. Future studies could focus on sustainable donor-funded procurement to determine how the Triple Bottom Line Approach may impact the procurement of laboratory equipment and other supporting commodities
A thesis submitted in partial fulfilment of the requirements for the Degree of Doctor of Philosophy (PhD) in Management, to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Donor-funded procurement; Operational effectiveness; Transaction costy; SDG-16: Peace, justice and strong institutions